Le gouvernement socialiste espagnol et la participation à l’Alliance atlantique depuis novembre 1982 (Note) - Labatut, Bernard (Études internationales, 1985)
The United Nations adopted the Law of the Sea Convention (LOSC) on April 30, 1982 but the saga began in 1967 when Arvid Pardo, the Permanent Representative of Malta to the United Nations, called for a constitution for the oceans of the world and a charter for its sea-bed, its resources, its subsoil and the air above it. The third United Nations Law of the Sea Conference (UNCLOS III) was convened in 1973 and terminated in the historic vote at New York on April 30, 1982 where 130 nations voted for the Law of the Sea Convention, only four voted against and seventeen abstained. The Law of the Sea Convention is a giant step forward in world and human affairs because it is concerned with sharing the earth's underwater resources amongst the earth's inhabitants rather than on the basis of first come/first served. The Convention controls, protects, shares and develops the oceans for all mankind. Questions of 12 mile limits, exclusive economic zones, continental shelves, territorial water rights of transit and innocent passage are also dealt with. Much old law is codified, much new law is created and even for non signatories there is much new customary international law. The Law of the Sea Convention is perhaps the greatest legislative triumph of the United Nations in its 40 year history.